How The Role of online and viral marketing and competitiveness ability on business performance of SMEs - Mochammad Jasin (AGUSPATI RESEARCH INSTITUTA, 2022)
The purpose of this study is to analyze the relationship of viral marketing to business performance, competitive ability has an effect on business performance. This study takes SMEs in Indonesia, with research variables are viral marketing message strategies, competitiveness ability, and business performance. This research method is quantitative, the research population is all SME consumers who are social media users who have seen SME marketing advertisements. The sample was recruited purposively with the qualifications of respondents who had only seen marketing advertisements from these SME vendors based on references from those who had filled out the questionnaire (snowball technique) and artial Least Square) using SmartPLS 3. The results obtained are viral marketing messages affect business performance, viral marketing messages affect business performance, competitiveness ability affects business performance.